2002
DOI: 10.1007/s00113-002-0427-2
|View full text |Cite
|
Sign up to set email alerts
|

Korakoidpseudarthrose nach Fraktur des Processus coracoideus bei anteriorer Schulterluxation

Abstract: Fractures of the coracoid process are rare and represent only 2-5% of all fractures of the scapula. The most frequent cause of a coracoid fracture is direct trauma, but indirect trauma may also lead to a fracture of this kind. Avulsion injuries as part of an acromioclavicular dislocation are the most frequent forms of trauma. For the rare cases of an anterior shoulder dislocation with concomitant coracoid fracture, two different mechanism are discussed. One cause of the coracoid fracture could be direct impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…It is thus inferred that the same mechanism might have operated in the formation of symptoms in the painful cases of chronic coracoid fracture Ogawa et al The Journal of TRAUMA ® Injury, Infection, and Critical Care • Volume 67, Number 5, November 2009 reported in the past. 10,12,13 Reattachment of the fragment to the original site or, as in the present series, releasing of the coracoacromial ligament to enable changing the displaced direction of the fragment into a downward direction is considered a reasonable therapeutic approach. Our study has certain limitations.…”
Section: Discussionmentioning
confidence: 96%
“…It is thus inferred that the same mechanism might have operated in the formation of symptoms in the painful cases of chronic coracoid fracture Ogawa et al The Journal of TRAUMA ® Injury, Infection, and Critical Care • Volume 67, Number 5, November 2009 reported in the past. 10,12,13 Reattachment of the fragment to the original site or, as in the present series, releasing of the coracoacromial ligament to enable changing the displaced direction of the fragment into a downward direction is considered a reasonable therapeutic approach. Our study has certain limitations.…”
Section: Discussionmentioning
confidence: 96%
“…Type 1 fracture of coracoid base, fracture line passes posterior to coracoclavicular ligament, needs operative fixation [ 1 ], whereas type 2 is avulsion type injury of coracoid tip fracture involving anterior to coracoclavicular ligament can be treated conservatively [ 1 ]. According to Goss et al, type 1 is avulsion type fracture anterior to coracoclavicular ligament, which may result in painful non-union or may prevent humeral head reduction [ 1 , 13 ]. Although there is conflict do exist literature regarding coracoid fracture management if coracoid fracture fixation is feasible in young active individuals prevent painful non-union, or if associated with glenoid deformity, AC joint injury, floating shoulder [ 1 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…A surgeon can consider operative treatment using either internal fixation or the Latarjet procedure when the acute glenoid rim defect is larger than 5% in an active patient [1]. A type II coracoid process fracture can be treated conservatively, but some studies report that a coracoid pseudoarthrosis can occur when there is a concomitant anterior shoulder dislocation [10]. A few cases of shoulder dislocations with a simultaneous fracture of the coracoid process have been previously reported in the literature [11].…”
Section: Discussionmentioning
confidence: 99%
“…Type II fractures (fractures distal to the coracoclavicular ligaments) can be treated conservatively. However, Kälicke et al [10] reported that a coracoid pseudoarthrosis could be caused by tension of the conjoined tendons in an anterior shoulder dislocation with a concomitant type II coracoid fracture. Therefore, surgical treatment should be considered to prevent pseudoarthrosis or nonunion in type II fractures with displacement greater than 5 mm.…”
Section: Discussionmentioning
confidence: 99%